Alterations in the saliva microbiome in patients with gastritis and small bowel inflammation. (April 2022) - Chen, Ming; Fan, Hui-Ning; Chen, Xiao-Yu; Yi, You-Cai; Zhang, Jing; Zhu, Jin-Shui
Abstract: The oral microbiome is an important part of the human microbiome. Accumulating data have shown that oral microbiome alterations are closely related to multiple human diseases. However, salivary microbiota distributions remain unclear in patients with gastritis and small bowel inflammation. Magnetically guided capsule endoscopy (MGCE) is a noninvasive diagnostic tool for patients with gastritis and small bowel inflammation. Herein, we analysed the alterations in saliva microbiota in the normal, small intestinal inflammation and chronic gastritis groups through 16S rRNA gene amplicon sequencing. We found that the abundance of Lactobacillaceae was dramatically higher in chronic gastritis group than healthy individuals (p = 0.001). The levels of Porphyromonas and Faecalibaculum in gastritis samples were increased (p = 0.028; p = 0.006), and the enrichments of Faecalibaculum and Kosakonia in small intestine inflammation samples were elevated (p < 0.001; p = 0.002) compared to those in normal individuals. Our findings clarify the saliva microbiota components and their importance of specific bacteria in gastritis and small bowel inflammation. Highlights: MGCE is a noninvasive diagnostic tool for patients with gastritis and small bowel inflammation. Herein, we analysed the alterations in saliva microbiota in the normal, small intestinal inflammation and gastritis groups through 16S rRNA gene amplicon sequencing. Our findings clarify the saliva microbiota components and their importance of specific bacteria in gastritis and small bowel inflammation.